Analysis Of The Effect Of Product Quality On Consumer Purchasing Decisions At Rr Collection Soppeng District - Surianti Surianti; Verri Ginoga; Asmiah Asmiah (GENTARA: management and accounting research, 2025)
The main problem in this study is whether product quality affects consumer purchasing decisions at RR Collection Soppeng Regency, while the purpose of this study is to determine the effect of product quality on consumer purchasing decisions at RR Collection Soppeng Regency. This research was conducted at the RR Collection which is located in Cabenge, Cabenge Village, Lilirilau District, Soppeng Regency, South Sulawesi Province. the population in this study were all customers at the RR Collection, Determination of samples using Purposive Sampling and Convinience Sampling techniques. Purposive Sampling is a sample selection of consumers based on objectives, so the number of samples in this study were 100 Respondents. To determine the effect of Product Quality on purchasing decisions, simple linear regression analysis is used. Based on the results of the research analysis, it can be concluded that: Product quality has a positive and significant influence on consumer purchasing decisions at RR Collection Soppeng Regency, which indicates that improving product quality aspects such as performance, features, reliability, and aesthetics directly increases consumer interest and decisions to buy these products. Based on the results of the conclusions stated above, the RR Collection Management is advised to continue to improve and maintain product quality through feature innovation, increased durability, and responsive after-sales service in order to strengthen positive consumer perceptions, increase loyalty, and maintain product competitiveness in the market.